Ginger as Anti-Inflammatory - Rossalia Artasya; Stefani Agustin Parapasan (Jurnal Penelitian Perawat Profesional, 2020)
Inflammation is the body's response to tissue damage where pro-inflammatory mediators are released. Several things can cause inflammation such as bacteria, virus, fungi, parasites, and it could also be due to the presence of foreign proteins, and the damage caused by the formation of tissue debris. Ginger has long been known as a spice plant that has the main content of gingerol and shogaol wich has potential as anti-inflammatory. This literature review was created using the latest research obtained from books, international journal, and website regarding the benefits of ginger and its anti-inflammatory effects. The year of publication of the literature used was 2010 to 2019, with 30 literatures was found, 24 literature were used as references and was analyzed using systemic literature review method. Various studies have stated that ginger has anti-inflammatory effects on the body. The gingerol and shogaol in ginger can suppress the production of nitric oxide and prostaglandins. Beside, ethyl acetate and nanoparticles in ginger can also reduce pro-inflammatory cytokines in the body.